A COMPARATIVE ANALYSIS OF PUBLIC SECTOR AUDITING: THE GAMBIA AND INDONESIA - Drammeh, Lamin K; Malik, Nazaruddin; Leniwati, Driana (Journal of Applied Finance and Accounting, 2025)
This study offers a comparative analysis of public sector auditing in The Gambia and Indonesia, focusing on how centralised versus decentralised governance structures influence audit effectiveness. A qualitative comparative case study approach was applied, using semi- structured interviews with audit professionals and document analysis of national audit laws, reports, and international standards. Data were analysed thematically to uncover patterns related to political interference, resource limitations, technological constraints and institutional capacity. Key findings indicate that The Gambia’s centralised system suffers from limited audit independence, weak legal protections, and poor documentation practices. In contrast, Indonesia’s decentralised structure results in inconsistent standards, regional technology gaps, and uneven training access. Both countries experience political interference and inadequate professional development, which undermine audit quality. The research contributes to the literature by linking governance structure to audit effectiveness and institutional transparency. It offers practical implications for policymakers, including the need for legal reforms, investment in digital infrastructure, improved public engagement, and standardised training programs. These findings support governance reforms aimed at strengthening accountability and sustainable development in emerging economies.